Human Monoclonal Antibodies as Adjuvant Treatment of Chronic Hepatitis B Virus Infection - Cerino, Antonella; Mantovani, Stefania; Mele, Dalila; Oliviero, Barbara; Varchetta, Stefania; Mondelli, Mario U. (Frontiers in Immunology, 2019)
Despite the availability of an effective prophylactic vaccine leading to sterilizing immunity, hepatitis B virus (HBV) is responsible for chronic liver disease in more than 250 million individuals, potentially leading to cirrhosis and primary liver cancer. Antiviral drugs able to completely suppress virus replication are indeed available but they are by and large unable to eradicate the virus. Several alternative new treatment approaches are currently being developed but none has so far captured the interest of clinicians for possible clinical development. A constant feature of chronic HBV infection is T-cell exhaustion resulting from persistent exposure to high antigen concentrations as shown by the high expression of programmed cell death protein 1 (PD-1) by HBV-specific CD8 T cells. One way of tackling this problem is to develop HBV-specific neutralizing antibodies that would clear excess envelope proteins from the circulation, allowing for nucleos(t)ide analogs or other antiviral drugs now in preclinical and early clinical development to take advantage of a reconstituted adaptive immunity. Several fully human monoclonal antibodies (mAb) have been developed from HBV-vaccinated and subjects convalescent from acute hepatitis B that show different properties and specificities. It is envisaged that such neutralizing mAb may be used as adjuvant treatment to reduce viral protein load, thus rescuing adaptive immunity in an effort to optimize the effect of antiviral drugs.